Analisis Struktur Melodi Lagu Dua Mata Saya Karya Pak Kasur - Fithri Meiliawati (UIN Sultan Maulana Hasanudin Banten, 2021)
A song masterpiece by Pak Kasur entitled Dua Mata Saya, My two eyes, is very interesting to be reviewed deeply. It can be seen from the structure of the melody and the lyric that has educational meaning and value. The method that is used in this research is descriptive analysis by collecting all the data and then the data are classified, validated and interpreted. This research shows that the melody structure that is made has clear pattern, the lyric is simple and easy hence children are able to pronounce it and it is appropriate according to the characteristic of children’s song.